Pendidikan Keagamaan Islam Dan Manajemen Kenabian - Hasbi Indra (IAIN Ponorogo, 2016)
Abstract: Islamic religious education is part of the national education system that play a role in the development of Indonesian nation in the future. Among the variants of Islamic religious education is the education of al-Quran, madrasah diniyah and pesantren. Referring to the quality of national education which is currently at the lowest level under the Southeast Asian countries such as Singapore, Malaysia, Thailand, Vietnam and the Philippines, it can be said the quality of Islamic religious education also can not be said to be satisfactory. Therefore, there should be efforts to improve the quality of religious educational institutions have to be able to compete with the future of education in developed countries. Graduates of Islamic religious education should equip themselves with a vast knowledge, professional attitude and mentally strong. One effort that should be considered in improving the quality of Islamic religious educational institutions is to implement the management of prophethood.Abstrak: Pendidikan keagamaan Islam merupakan bagian dari sistem pendidikan nasional yang berperan dalam pembangunan bangasa Indonesia dimasa yang akan datang. Diantara varian pendidikan keagamaan Islam adalah pendidikan al-Quran, madrasah diniyah dan pesantren. Merujuk pada kualitas pendidikan nasional yang saat ini berada di tingkat terbawah di bawah negara Asia Tenggara seperti Singapura, Malaysia, Thailand, Vietnam dan Filipina, maka dapat dikatakan kualitas pendidikan keagamaan Islam juga belum bisa dikatakan memuaskan. Oleh karena itu perlu ada upaya-upaya untuk meningkatkan kualitas lembaga pendidikan keagamaan ini ke depan agar mampu berkompetisi dengan pendidikan di negara-negara maju. Lulusan pendidikan keagamaan Islam harus membekali diri dengan pengetahuan yang luas, sikap profesional dan mental yang kuat. Salah satu upaya yang patut dipertimbangkan dalam meningkatkan kualitas lembaga pendidikan keagamaan Islam adalah dengan mengimplementasikan manajemen kenabian.